Пинч-реконструкция секций гидроочистки и каталитического риформинга на установке Л-35-11/600 - Ульев, Леонид Михайлович; Нечипоренко, Дарина Дмитриевна (НТУ "ХПИ", 2013)
У результаті застосування пінч-методів отримана нова система теплообміну для процесів гідроочищення і каталітичного риформінгу сировини на установці каталітичного риформінгу Л-35-11/600. Визначено зайві енерговитрати в існуючій схемі і проведена пінч-інтеграція як для кожного блоку окремо так і для спільного проекту реконструкції даних блоків. Впровадження пінч-проектування дозволяє знизити енергоспоживання для блоку гідроочищення сировини на 2,2 МВт. Для блоку каталітичного риформінгу енергоспоживання знижується на 6,4 МВт. Для спільної інтеграції блоків гідроочищення сировини і каталітичного риформінгу енергоспоживання знижується на 11,4 МВт. Була проведена порівняльна характеристика інтегрованих процесів. На основі економічно обґрунтованих розрахунків було зроблено висновок, що найбільш доцільним є проведення реконструкції для двох даних блоків спільно, а не окремо.

Pinch diagnostics for hydrotreating section and catalytic reforming section of catalytic reforming unit L-35-11/600 was carried out. Comparative economic analysis of their effectiveness after the proposed retrofit was performed for each section separately and for the total their flowsheet. The implementation of the pinch design allows to reduce power consumption for hydrotreating process by 2,2 MW, the payback period of the proposed project will be about 7 months. For the catalytic reforming section power consumption is reduced by 6,4 MW, the payback period of the proposed project will be about 10 months. Energy consumption for joint integration of hydrotreating section and catalytic reforming section reduced by 11,4 MW, the payback period of the proposed project will be about 8 months. Therefore, it was concluded that pinch design for these sections of catalytic reforming unit L-35-11/600 the most advisable to carry out for the two sections together.
Pinch reconstruction of hydrotreating and catalytic reforming sections on unit L35-11/600
Keywords: производство нефтепродуктов; деэтанизация; стабилизация катализата; технологическая схема; технологические потоки